1992
DOI: 10.1128/jb.174.19.6247-6255.1992
|View full text |Cite
|
Sign up to set email alerts
|

A chemotactic signaling surface on CheY defined by suppressors of flagellar switch mutations

Abstract: CheY is the response regulator protein that interacts with the flagellar switch apparatus to modulate flagellar rotation during chemotactic signaling. CheY can be phosphorylated and dephosphorylated in vitro, and evidence indicates that CheY-P is the activated form that induces clockwise flagellar rotation, resulting in a tumble in the cell's swimming pattern. The chemotaxis (Che) proteins couple flagellar rotation to the environment by transducing chemotactic signals from specific transmembrane chemoreceptors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
95
0

Year Published

1995
1995
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(99 citation statements)
references
References 56 publications
4
95
0
Order By: Relevance
“…Lack of metal ion binding to the mutant protein is consistent with the observation that in wild-type CheY, Asp 13 is directly involved in coordination of the Mg 2ϩ ion (15,16). Furthermore, D13K is phosphorylated only very slowly in the presence of the histidine protein kinase CheA and ATP (26,27), and apparently not at all in the presence of acetyl phosphate (34). Thus, crystallization of CheY D13K in the absence of both Mg 2ϩ and phosphate is biologically relevant.…”
Section: Methodssupporting
confidence: 67%
See 2 more Smart Citations
“…Lack of metal ion binding to the mutant protein is consistent with the observation that in wild-type CheY, Asp 13 is directly involved in coordination of the Mg 2ϩ ion (15,16). Furthermore, D13K is phosphorylated only very slowly in the presence of the histidine protein kinase CheA and ATP (26,27), and apparently not at all in the presence of acetyl phosphate (34). Thus, crystallization of CheY D13K in the absence of both Mg 2ϩ and phosphate is biologically relevant.…”
Section: Methodssupporting
confidence: 67%
“…Although the lysine side chain at position 13 appears capable of assuming an alternate rotameric position (t) away from the active site with no steric restrictions, its observed position (g Ϫ ) in the structure blocks access to the active site, especially the Mg 2ϩ binding region. This is consistent with the fact that the CheY D13K mutant does not bind Mg 2ϩ (34) and exhibits essentially no phosphorylation ability (26,27,34).…”
Section: å X-ray Structure Of Chey Mutant D13ksupporting
confidence: 69%
See 1 more Smart Citation
“…While we have no direct evidence for separate motors in R. centenum, we have observed that the polar and lateral flagella are composed of different flagellin and basal ring subunits (16,32). Evidence for different specificities of the R. centenum CheY homologs to the motor complex can also be obtained by inspection of the motor docking domains that have been identified by mutational and crystallographic analyses of CheY homologs from E. coli and S. typhimurium (31,37,38,43). As shown in the CheY alignment in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…3) They had previously been shown to have altered CheA binding (D93K, A90V, Y106W, V108M, F111V, and T112I) (35). 4) They had been identified as suppressors of mutations affecting the flagellar switch (A90V, V108M, F111V, T112I, E117K, and E27K) (9). To test the dephosphorylation rates of mutant CheY proteins, we first needed to know whether the mutant CheY proteins could be phosphorylated by CheA.…”
Section: In Vitro Phosphorylation and Dephosphorylation Of Mutantmentioning
confidence: 99%